Synthesis of Novel Quinazoline-4-one Derivatives and their Acyclonucleoside Analogs - A.-H. Zahran, Magdy; M. Ali, Omar; F. Zeid, Ibrahim; Rageb, Elham (Asian Journal of Chemistry, 2012)
A number of quinazolin-4-one derivatives were synthesized. Reaction of the 2-hydrazonoquinazoline-4-one derivatives with aldoses afforded the corresponding sugar hydrazones which on treatment with ferric chloride to afford the corresponding acyclic nucleoside analogues.